The role of supply chain management practices, supply chain responsiveness, and organizational capabilities on organizational performance - Rini, Poppy Laksita (Universitas Ahmad Dahlan, 2023)
Purpose-Several internal and external elements impact an organization's performance. This study examines organizations' performance using both internal and external elements. Organizational capabilities are the internal aspects of the study, whereas supply chain management practices and supply chain responsiveness are the external factors. These three elements are believed to have a significant impact on an organization's performance. Design/Methodology/Approach-The study population focused on furniture micro, small, and medium-sized enterprises in Yogyakarta, Indonesia. The research data were collected through questionnaires administered to respondents, and the results of 50 respondents were obtained. Then, a model analysis was applied using Smart PLS. Findings-Supply chain management practices positively impact organizational performance, and supply chain responsiveness improves organizational performance. Organizational capabilities also have a favorable effect on organizational performance. If these three elements can be effectively utilized, it will enhance organizational performance. Research limitations/implications-Micro, small, and medium-sized enterprises must understand the importance of supply chain management and maximize its use to promote improvements in organizational performance. Business actors must maximize their efforts to achieve organizational success by considering other aspects, such as organizational capabilities. Originality/value-Research on organizational performance is currently lacking, especially in the case of micro, small, and medium-sized enterprises that are specifically associated with particular industries. Government rules, strategy orientation, and green supply chain management are just a few of the external and internal factors that have been the subject of prior research on organizational performance. As a result, this study examines the characteristics of supply chain management practices, supply chain responsiveness, and organizational capabilities in order to measure the performance of furniture micro, small, and medium-sized enterprises in Yogyakarta, Indonesia.